A Toolkit for Orthogonal and in vivo Optical Manipulation of Ionotropic Glutamate Receptors - Levitz, Joshua; Popescu, Andrei T.; Reiner, Andreas; Isacoff, Ehud Y. (Frontiers in Molecular Neuroscience, 2016)
The ability to optically manipulate specific neuronal signaling proteins with genetic precision paves the way for the dissection of their roles in brain function, behavior, and disease. Chemical optogenetic control with photoswitchable tethered ligands (PTLs) enables rapid, reversible and reproducible activation or block of specific neurotransmitter-gated receptors and ion channels in specific cells. In this study, we further engineered and characterized the light-activated GluK2 kainate receptor, LiGluR, to develop a toolbox of LiGluR variants. Low-affinity LiGluRs allow for efficient optical control of GluK2 while removing activation by native glutamate, whereas variant RNA edited versions enable the synaptic role of receptors with high and low Ca2+ permeability to be assessed and spectral variant photoswitches provide flexibility in illumination. Importantly, we establish that LiGluR works efficiently in the cortex of awake, adult mice using standard optogenetic techniques, thus opening the door to probing the role of specific synaptic receptors and cellular signals in the neural circuit operations of the mammalian brain in normal conditions and in disease. The principals developed in this study are widely relevant to the engineering and in vivo use of optically controllable proteins, including other neurotransmitter receptors.